Law Enforcement Against Abuse of Authority by The Lurah in Issuing Multiple Certificates (Case Study in Medokan Subdistrict, Surabaya) - Estuanti, Ananda; Arifulloh, Achmad; Laksana, Andri Winjaya (TABELLIUS: Journal of Law, 2026)
This study examines the enforcement of law against the abuse of authority by a village head (lurah) in the issuance of double land certificates, with a case study in Medokan Subdistrict, Surabaya. The issue of double certificates represents a serious failure in land administration that directly undermines legal certainty and the protection of community land rights. In practice, the issuance of double certificates is often linked to the abuse of authority by local government officials through manipulation of juridical data, issuance of unlawful land statements, and disregard for the principle of prudence in public service. This research employs an empirical juridical method with a qualitative approach, combining statutory analysis with an examination of legal practices in the field. Data were collected through literature review, legal documents, and analysis of relevant empirical facts. The findings indicate that weak supervision, low integrity of officials, and an underdeveloped land administration system are the main factors contributing to the occurrence of double certificates. Law enforcement against officials who abuse their authority still faces significant obstacles, particularly in terms of evidence and inter-agency coordination. This study is expected to contribute academically to the development of notarial and land law, as well as provide practical recommendations for improving land administration governance based on legal certainty and justice.